Correction to: Mediation criteria for interactive serious games aimed at improving learning in children with attention deficit hyperactivity disorder (ADHD) - Teresa Coma-Roselló; Ana Cristina Blasco-Serrano; María Ángeles Garrido Laparte; Antonio Aguelo Arguis (The Asia-Pacific Society for Computers in Education (APSCE), 2021)
An amendment to this paper has been published and can be accessed via the original article.